Identification of microRNAs implicated in modulating resveratrol-induced apoptosis in porcine granulosa cells - Zhang, Huibin; Wang, Jinglin; Xie, Fan; Liu, Yangguang; Qiu, Mengyao; Han, Zheng; Ding, Yueyun; Zheng, Xianrui; Yin, Zongjun; Zhang, Xiaodong (Frontiers in Cell and Developmental Biology, 2023)
MicroRNAs (miRNAs) are small, noncoding RNAs that play a crucial role in the com-plex and dynamic network that regulates the apoptosis of porcine ovarian granulosa cells (POGCs). Resveratrol (RSV) is a nonflavonoid polyphenol compound that is in-volved in follicular development and ovulation. In previous study, we established a model of RSV treatment of POGCs, confirming the regulatory effect of RSV in POGCs. To investigate the miRNA-level effects of RSV on POGCs to reveal differentially expressed miRNAs, a control group (n = 3, 0 μM RSV group), a low RSV group (n = 3, 50 μM RSV group), and a high RSV group (n = 3, 100 μM RSV group) were created for small RNA-seq. In total, 113 differentially expressed miRNAs (DE-miRNAs) were identified, and a RT-qPCR analysis showed a correlation with the sequencing data. Functional annotation analysis revealed that DE-miRNAs were mainly involved in cell development, proliferation, and apoptosis in the LOW vs. CON group. In the HIGH vs. CON group, functions were associated with metabolic processes and responses to stimuli, and pathways were related to PI3K-Akt, Wnt, and apoptosis. In addition, we constructed miRNA-mRNA networks related to Apoptosis and Metabolism. Then, ssc-miR-34a and ssc-miR-143-5p were selected as key miRNAs. In conclusion, this study provided an improved understanding of effects of RSV on POGCs apoptosis through the miRNA modulations. These results suggested that RSV could promote POGCs apoptosis by stimulating the miRNA expressions, and provided a better understanding of the role of miRNAs combined with RSV in ovarian granulosa cell development in pigs.